Asuransi Syariah Digital sebagai Pilar Keberlanjutan Ekonomi Hijau dan Biru Berbasis Maqasid al-Shariah - Soeharjoto Soeharjoto; Debbie Aryani Tribudhi; Deni Mukti Hidayat; Adi Rosyadi; Teguh Supriyadi; Saiful Ali (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
At this era, global economic development is shifting toward sustainable development. This phenomenon demands a financial system capable of managing long-term environmental risks to support the green and blue economic transformation. This research aims to conceptually examine the role of digital Islamic insurance as a strategic instrument in the sustainable Islamic economic and financial system. Conceptual qualitative is the method of this research, through a review and synthesis of literature on Islamic insurance, digital technology, green economy, blue economy, and maqasid al-shariah. The results show that digital sharia insurance is not only a technological innovation in the sharia insurance industry, but also functions as a sustainable risk mitigation infrastructure. Through risk-sharing mechanisms, increased Islamic financial inclusion, and adaptive protection against environmental and marine risks, in this case digital sharia insurance also supports green investment, strengthens the marine-based economy, and increases the resilience of vulnerable communities. The integration of digital technology and sharia principles further underscores the potential of digital Sharia insurance as an important pillar in a fair, inclusive, and long-term welfare-oriented Islamic financial system.